The influence of gratitude on patriotism among college students: a cross-sectional and longitudinal study - Hu, Yunjun; Zhang, Huilin; Zhang, Wei; Li, Qian; Cui, Guanyu (Frontiers in Psychology, 2024)
Introduction Patriotism, a positive emotional attachment to one’s country, has been associated with prosocial behavior, social responsibility, and gratitude. It plays a crucial role in promoting social harmony and national development. However, the factors influencing patriotism and their mechanisms remain unclear. This research consists of two studies exploring the internal mechanisms that connect gratitude and patriotism. Methods Study 1 conducted a cross-sectional analysis among 3,826 college students to investigate the influence of gratitude on patriotism, emphasizing the mediating role of general life satisfaction and the moderating impact of socioeconomic status. This approach aimed to elucidate the complex relationships between these variables within college students. Study 2 adopted a longitudinal approach, surveying 905 college students across three-time points. This study was designed to explore the temporal mediation of general life satisfaction in the gratitude-patriotism relationship, offering insights into the evolution of these constructs over time. The sequential surveys aimed to capture the dynamic nature of gratitude’s impact on patriotism, considering the continuous interplay with general life satisfaction among college students. Results Study 1 reveals a noteworthy finding: Gratitude enables the direct prediction of patriotism, while additionally, general life satisfaction plays a role between them. Furthermore, the predictive effect of gratitude on patriotism is strengthened among individuals with higher levels of socioeconomic status. However, there is no significant moderating effect between general life satisfaction and patriotism by socioeconomic status. Study 2 demonstrates that general life satisfaction plays a significant mediating role in the relationship between gratitude and patriotism, over a period of three times. However, the moderating influence of socioeconomic status was not substantiated in the longitudinal mediation model. Conclusion These two studies shed light on the complex relationship between gratitude and patriotism. They emphasize the significance of gratitude, general life satisfaction, and socioeconomic status in shaping patriotism, offering potential avenues for understanding the internal mechanisms that influence patriotism.